The Use of Interactive Digital Learning Media to Enhance Primary School Pupils’ Motivation to Learn - Dahlan, Taufiqulloh; Hermawan, Alecia Zahra Putri; Khovita, Indah; Parlina, Irna; Zulkaisnaeni, Nafla; Widya, Delya Risky; Surya, Dimas (IDRIS Darulfunun Institute, 2026)
This study aims to analyse the use of interactive digital learning media at primary school level, examine its impact on pupils’ learning motivation, and identify the factors influencing the effectiveness of its use. This study employs a qualitative approach using library research, in which data were obtained from various academic sources, including journal articles, academic books, and relevant research reports. Data analysis was conducted using content analysis to identify patterns, relationships, and trends in findings related to the use of interactive digital media in learning. The results of the study indicate that interactive digital learning media contribute significantly to enhancing students’ learning motivation through the presentation of interactive, multimodal, and contextual material, thereby encouraging active engagement and strengthening intrinsic motivation. However, the effectiveness of its use is influenced by various factors, including teachers’ digital and pedagogical competencies, the availability of technological infrastructure, the quality of media design, as well as policy support and the school environment. The implications of this research underscore the importance of systematically planning and implementing interactive digital media in accordance with pedagogical principles in order to achieve optimal learning outcomes. The novelty of this research lies in its comprehensive synthesis of the latest literature, which provides a holistic perspective on the role of interactive digital media in enhancing primary school pupils’ motivation to learn, as well as serving as a conceptual foundation for the development of innovative and adaptive learning strategies